Enhancing the effects of exfoliated carbon nanofibers using bone morphogenetic protein in a rat spinal fusion model. Issue 11 (23rd July 2018) - Notani, Naoki; Miyazaki, Masashi; Toyoda, Masahiro; Kanezaki, Shozo; Ishihara, Toshinobu; Tsumura, Hiroshi
ABSTRACT: Exfoliated carbon nanofibers (ExCNFs) are expected to serve as excellent scaffolds for promoting and guiding bone‐tissue regeneration. We aimed to enhance the effects of ExCNFs using bone morphogenetic proteins (BMPs) and examined their feasibility and safety in clinical applications using a rat spinal fusion model. Group I ( n = 15) animals were implanted with the control carrier; Group II ( n = 16) animals were implanted with carrier containing 1 μg ExCNFs; Group III ( n = 16) animals were implanted with carrier containing 1 μg recombinant human (rh) BMP‐2; and Group IV ( n = 17) animals were implanted with carrier containing 1 μg rhBMP‐2 and 1 μg ExCNFs. The rats were euthanized after 4 or 8 weeks and their spines were explanted and assessed by manual palpation, radiographs, and high‐resolution microcomputerized tomography (micro‐CT); the spines were also subjected to histological analysis. The fusion rates in Group IV (25.0%: 4‐week, 45.5%: 8‐week) were considerably higher than in Groups I (0%: 4‐week, 0%: 8‐week), II (0%: 4‐week, 15.0%: 8‐week), and III (16.7%: 4‐week, 30.0%: 8‐week). These results demonstrated the enhancement of ExCNF bone fusion effects by BMP in a rat spinal fusion model. Our results suggest that the enhancement of ExCNFs effects by BMP makes this combination a possible attractive therapy for spinal fusion surgeries. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2892–2900, 2018.